Election Hoax Detection on X using CNN with TF-RF and TF-IDF Weighting Features - Adelia, Dila; Astuti, Widi; Lhaksmana, Kemas Muslim (Journal of Computer System and Informatics (JoSYC), 2024)
X social media is a microblogging platform for sharing brief thoughts and trends. It has become a focal point for expressing political views. The increased political engagement on X social media has facilitated the swift and extensive sharing of ideas. Still, it also brings the risk of spreading false information and hoaxes that can manipulate public opinion. Preventing fake news on social media is crucial because it can influence election outcomes and social stability. For example, X social media has been used during elections to spread hoaxes, such as false claims of vote tampering or misleading information about candidate qualifications. This study implements a Convolutional Neural Network (CNN) due to its advantages in recognizing complex patterns and achieving high performance in tasks like classification. The dataset used in this study consists of 2,670 tweets. The dataset is divided into three subsets: 60% for training, 20% for testing, and 20% for validation. It also uses Term Frequency Relevance Frequency (TF-RF) and Term Frequency Inverse Document Frequency (TF-IDF) weighting features to improve accuracy in detecting fake news. This study compares the TF-RF and TF-IDF weighting features using the CNN classification method on the topic of the 2024 election. The testing results indicate that both TF-RF and TF-IDF achieved similar overall performance, with TF-RF slightly excelling in recall and F1-score. At the same time, TF-IDF showed a marginally higher precision.